The antepartum stillbirth syndrome: risk factors and pregnancy conditions identified from the INTERGROWTH‐21st Project. (28th December 2016) - Hirst, JE; Villar, J; Victora, CG; Papageorghiou, AT; Finkton, D; Barros, FC; Gravett, MG; Giuliani, F; Purwar, M; Frederick, IO; Pang, R; Cheikh Ismail, L; et al.
Tweetable abstract: International stillbirth study finds individual risks poor predictors of death but combinations promising. Abstract : Objectives: To identify risk factors for antepartum stillbirth, including fetal growth restriction, among women with well‐dated pregnancies and access to antenatal care. Design: Population‐based, prospective, observational study. Setting: Eight international urban populations. Population: Pregnant women and their babies enrolled in the Newborn Cross‐Sectional Study of the INTERGROWTH‐21 st Project. Methods: Cox proportional hazard models were used to compare risks among antepartum stillborn and liveborn babies. Main outcome measures: Antepartum stillbirth was defined as any fetal death after 16 weeks' gestation before the onset of labour. Results: Of 60 121 babies, 553 were stillborn (9.2 per 1000 births), of which 445 were antepartum deaths (7.4 per 1000 births). After adjustment for site, risk factors were low socio‐economic status, hazard ratio (HR): 1.6 (95% CI, 1.2–2.1); single marital status, HR 2.0 (95% CI, 1.4–2.8); age ≥40 years, HR 2.2 (95% CI, 1.4–3.7); essential hypertension, HR 4.0 (95% CI, 2.7–5.9); HIV/AIDS, HR 4.3 (95% CI, 2.0–9.1); pre‐eclampsia, HR 1.6 (95% CI, 1.1–3.8); multiple pregnancy, HR 3.3 (95% CI, 2.0–5.6); and antepartum haemorrhage, HR 3.3 (95% CI, 2.5–4.5). Birth weight <3rd centile was associated with antepartum stillbirth [HR, 4.6 (95% CI, 3.4–6.2)]. The greatest risk was seen in babies not suspected to have been growth restricted antenatally, with an HR of 5.0 (95% CI, 3.6–7.0). The population‐attributable risk of antepartum death associated with small‐for‐gestational‐age neonates diagnosed at birth was 11%. Conclusions: Antepartum stillbirth is a complex syndrome associated with several risk factors. Although small babies are at higher risk, current growth restriction detection strategies only modestly reduced the rate of stillbirth. Tweetable abstract: International stillbirth study finds individual risks poor predictors of death but combinations promising.